Analysis of Influencing Factors Efficiency of the Loading and Unloading Process at MT. Patra Tanker 3 - Fadhilah Rezky Marshanda; Hadi Setiawan; Nurul Fadliana (Institut Nalanda, 2026)
Cargo discharge operations on tanker vessels play a vital role in national energy distribution and require high efficiency without compromising safety standards. In practice, MT. Patra Tanker 3, operated by PT Pertamina International Shipping, experiences recurring technical and operational constraints that may significantly reduce discharge efficiency and increase operational risk. This study aims to identify and analyze the influencing factors and formulate strategic optimization recommendations. A qualitative descriptive approach was applied through direct field observation, in-depth semi-structured interviews with key crew members, and documentation review during sea practice from August 2024 to August 2025. Data were analyzed using reduction, display, and conclusion drawing techniques. The findings reveal that discharge efficiency is influenced by three interrelated factors: technical factors (valve and seat ring condition affecting system pressure stability), human factors (inter-station coordination quality and crew fatigue during prolonged operations), and managerial factors (maintenance system effectiveness and operational supervision). These factors do not operate in isolation but interact dynamically within a socio-technical system. Optimization requires strengthened preventive maintenance on critical components, improved communication protocols between work stations, and systematic continuous evaluation in accordance with the ISM Code and ISGOTT international standards.